Reduksi Purin pada Emping Melinjo Melalui Pre-treatment Perendaman Emping Mentah - Hanifah Nuryani Lioe; Dahrul Syah; Annisa Defriana (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2019)
Melinjo chips (emping as local name) has high purine content which can be related to the high uric acid level in blood that lead to joint inflamation due to the sendimentation of uric acid. The objective of this research is to prove that soaking process can reduce purine content in emping and to know the effect of the soaking process length in purine reduction. Soaking time (2, 5, and 12 hours) and emping brand (Sriti, A1 and Koki) were used as the treatments. Purine compounds such as adenine and hypoxanthine were analyzed by using High Performance Liquid Chromatography (HPLC) method with C18 column and UV detector. The three emping samples were also analyzed by using sensory evaluation to know the consumer preference toward the treated fried emping. Results obtained from this research were that soaking process can reduce both adenine and hypoxanthin content in emping. Soaking for 2 hours in water could reduce adenine content 13 – 39% and hypoxanthine content 4 – 60%. Soaking process for 2 hours on emping could reduce up to 50% of total purine base content in A1 brand, however, soaking time was not directly proportional to the decrease in purine levels. Purine content after 5 and 12 hours soaking tend to be fluctuative. Emping samples that were soaked in the water have a decrease in preference by the panelists either in color, aroma, taste, texture or in overall, but still accepted by panelists.